1977
DOI: 10.1084/jem.145.3.749
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding property of Sm nuclear antigen.

Abstract: Antibodies to nuclear antigens are detected frequently in the sera of patients with systemic lupus erythematosus (SLE) and related autoimmune diseases. These antibodies have multiple immunochemical specificities and they react with different macromolecular components of cell nuclei (1), among which are nonhistone or nuclear acidic proteins. The first nuclear acidic protein characterized immunochemically with the aid of spontaneously occurring antibodies was called Sm nuclear antigen (2). Subsequently, other nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Some of the differences in the findings may be related to the fact that the nuclear antigens may be present in the native state as molecules associated with one another in larger-complexed particles . In a previous study, it was shown that the Sm protein had DNA-binding property and bound more tightly to single-strand DNA than to double-strand DNA (24). Although binding to RNA was not studied, it is possible that Sm protein might bind to RNA molecules in the cell nucleus, and at least some Sm molecules may be associated with RNA protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the differences in the findings may be related to the fact that the nuclear antigens may be present in the native state as molecules associated with one another in larger-complexed particles . In a previous study, it was shown that the Sm protein had DNA-binding property and bound more tightly to single-strand DNA than to double-strand DNA (24). Although binding to RNA was not studied, it is possible that Sm protein might bind to RNA molecules in the cell nucleus, and at least some Sm molecules may be associated with RNA protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown previously that single-stranded or dsDNA can bind to Sm proteins. 10 Also, the reactivity of anti-dsDNA-positive sera from patients with SLE with the SmD1(83-119) peptide was much lower after DNaseI treatment of the blocking reagent, although in particular anti-dsDNA-negative anti-SmD-positive sera from patients with SLE retained their reactivity. These data may explain that the use of different ELISA methods may lead to great differences (36-70%) in the prevalence of anti-SmD1(83-119) reactivity in patients with SLE.…”
Section: Discussionmentioning
confidence: 95%
“…A precondition for these models is that the highly positively charged SmD1 83–119 or SmD1 molecules bind to DNA and do not critically impair the binding of DNA to anti‐dsDNA antibodies on the B cell surface. Several groups (26, 27) have hypothesized that such SmD1–dsDNA complexes are targets for both anti‐dsDNA and anti‐Sm responses. Our previous studies demonstrated that the addition of dsDNA to SmD1 increased the frequency of SmD1‐reactive T cells in human SLE (17).…”
Section: Discussionmentioning
confidence: 99%